2021
DOI: 10.1093/ckj/sfab264
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and long COVID among the UK nephrology workforce: results from a national survey investigating the impact of COVID-19 on working lives

Abstract: Background The COVID-19 pandemic is placing a significant strain on healthcare. We conducted a national survey of the UK nephrology workforce to understand its impacts on their working lives. Methods An online questionnaire incorporating the Maslach Burnout Inventory Score was distributed between 31st March and 1st May 2021, with a focus on COVID-19 and long COVID incidence, vaccine uptake, burnout, and working patterns. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Although their education was maintained overall, 42% of fellows reported a negative impact of the pandemic on their overall quality of life, 33% reported a poorer work–life balance, and 15% scored as experiencing high distress measured using the Resident Well-Being Index. Similar findings were seen for trainees in the UK 154 , France and Belgium 155 .…”
Section: Trainee Educationsupporting
confidence: 82%
“…Although their education was maintained overall, 42% of fellows reported a negative impact of the pandemic on their overall quality of life, 33% reported a poorer work–life balance, and 15% scored as experiencing high distress measured using the Resident Well-Being Index. Similar findings were seen for trainees in the UK 154 , France and Belgium 155 .…”
Section: Trainee Educationsupporting
confidence: 82%
“…The UK report was not focused specifically on hemodialysis personnel, which may explain the higher rates of participants perceiving low personal accomplishment in our cohort. Selvaskandan et al found that burnout was more common among younger respondents and those with long COVID [ 22 ]. In our survey, we did not address long COVID specifically, but we did not observe associations between burnout and SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout among nephrologists has been an increasingly discussed topic in recent years, which indicates a growing understanding of its relevance for both patient satisfaction [ 19 ] and the nephrology workforce [ 20 ]. The influence of the current pandemic on burnout among renal healthcare professionals has so far only been addressed in two reports—the international survey on COVID-19 experiences which enrolled mostly nurses [ 21 ] and the national UK report on the influence of long COVID-19 on burnout and work life among the nephrology workforce [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…At a more fundamental level, fostering individuality is fundamental to trainee well-being and job satisfaction [ 23 , 24 ]. This is particularly important for preventing workforce attrition in the context of the COVID-19 pandemic, where burnout levels and plans for early retirement are at a high [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could reduce morale, increase burnout, and at worst, lead to poorer patient care [ 7 10 ]. Such disparities are critical to address, especially in the context of the on-going COVID-19 pandemic, which has negatively impacted trainee morale and increased the risk of attrition within the UK nephrology workforce [ 11 ].…”
Section: Introductionmentioning
confidence: 99%